Effects of the Baking Process on the Chemical Composition, Sensory Quality, and Bioactivity of Tieguanyin Oolong Tea - Gao, Ying; Cao, Qing-Qing; Chen, Yu-Hong; Granato, Daniel; Wang, Jie-Qiong; Yin, Jun-Feng; Zhang, Xue-Bo; Wang, Fang; Chen, Jian-Xin; Xu, Yong-Quan (Frontiers in Nutrition, 2022)
Tieguanyin oolong tea (TOT), a semi-oxidized tea originating from Anxi county in China, is categorized into jade TOT, medium-baked TOT, and deep-baked TOT, based on different baking processes. To study the effects of baking, chemical analysis, sensory evaluation, and bioactivity assessments of the three TOTs were conducted. The results indicated that the baking process promoted the formation of colored macromolecules (e.g., theabrownins), which affected the color of tea infusion. Free amino acids underwent the Maillard reaction and generated specific Maillard reaction products, such as 5-hydroxymethylfurfural and furfural, which modified the taste and aroma. Floral and fresh volatiles were remarkably reduced, while multiple new volatiles were produced, forming a typically baked aroma. The antioxidant activity and antibacterial activity were reduced after baking, which might be associated with the decrease of monomeric catechins. These results provide a scientific basis for understanding the changes caused by the baking process.